LEARNING IDENTITY OF ARABIC SPEAKING COUNTRIES STUDENTS IN MAULANA MALIK IBRAHIM STATE ISLAMIC UNIVERSITY OF MALANG - Rosi, Rois Imron (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Learning identity is very crucial to help students achieving their success. By understanding student’s learning identity, lecturer can provide an appropriate teaching method in the classroom. Cognitively, by implementing an appropriate teaching method based on learning identity, students will easily understand the material. This study explored Arabic speaking countries students because the increasing number of foreign students studying in Maulana Malik Ibrahim State Islamic University in 2023. Among those foreign students in this university, 52% of them are coming from Arabic speaking countries. So that, exploring their learning identity will be crucial to develop learning quality and gaining international reputation. This study examined seven Arabic speaking countries students coming from Yemen, Algeria, Sudan, and Egypt. By using qualitative research with phenomenological design, this study tried to explore student’s learning identity as well as their supporting and barrier factor in experiencing teaching and learning in university. The result of this study identified four learning identities of Arabic speaking countries students those are: between active and passive student, memorizing learner, lover of writing, and Arabic language lover. During their study in Indonesia, they faced some supporting and barrier factor of teaching and learning in university. The supporting factor came from internal motivation, family support, and conducive environment, while barrier factor came from Indonesian language alphabet and Indonesian style of learning. Findings of this study certainly will enrich the literature on Arabic speaking countries students’ learning identity.